Heidegger and Augustine. Memory, Temptation, Time - Esposito, Constantino (Pensamiento. Revista de Investigación e Información Filosófica, 2014)
The article deals with Augustine’s presence in Heidegger’s thought. Indeed, Augustine is not only one of the main sources for the young Heidegger’s training (together with Husserl’s phenomenology and Aristotle’s philosophy), but he is also the fundamental inclination, sometimes hidden, that Heidegger tries to absorb and metabolize in his own thought. The Confessions’ interpretation – in particular the reading of book X on memoria and temptatio and book XI on time – constitutes Heidegger the occasion to make some basic theoretical decisions. Man is nothing but an historical and temporal being-there who raises the question of being because he is in himself that question. While for Augustine the question is raised before a You, in Heidegger’s thought the question of man – i.e. the question that man is – is handed over to «nothing», because the mystery of being can never become a presence. The possibility of a confession, as a dramatic dialogue between the I and the presence of being, becomes for Heidegger the sign of the finitude of the being-there and the impossibility of being in itself. So the famous start of the Confessions («… for Thou madest us for Thyself, and our heart is restless, until itreposes in Thee») in Heidegger’s perspective should be translated as follows: and our heart is restless, until it reposes in itself.